PELAKSANAAN PERJANJIAN PAKET PEKERJAAN KONSULTANSI ANTARA SATUAN KERJA NON VERTIKAL TERTENTU PERENCANAAN DAN PENGAWASAN JALAN NASIONALPROVINSI JAMBI DENGAN PT. ARTERI CIPTA RENCANA JO PT. RAISSA GEMILANG - Fitri Aulia Simatupang; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 1320 of the Civil Code regarding the terms of the agreement, in which the cooperation agreement occurs between the parties. The agreement between the two parties about the importance of the rights and interests of each party involved in the agreement. The agreement applies as binding on the parties that replace it with the requirements in Article 1338 of the Civil Code. The problems examined in this study, namely the implementation of the agreement of supervision of the Jambi Province between the Directorate General of Highways and PT. Arteri Cipta Rencana with what was caused by one party to default on the other party. This writing uses sociological research methods that support the provision of opinions, explain and question about those who support. This type of research is classified as observational research conducted by survey, namely research directly to the research location using data collection tools in the form of interviews, whereas when viewed from its nature, this writing is descriptive analysis, which means the research is intended to provide an overview detailed, clear and systematic about the main problems of research. Soerjono Soekanto and Sri Mamudji suggested that descriptive research is a study that intends to provide as detailed data as possible about humans, circumstances or other symptoms, with a view to reinforcing hypotheses, to reinforce a theory or formulate new theories. Based on the results of the study it can be concluded that the rights and obligations in the Consultation Work Package Agreement between the Specific Non Vertical Work Unit Planning and Supervision of the Jambi Provincial National Road and PT. Arteri Cipta Rencana Jo PT. Raissa Gemilang said that the rights and obligations of the parties are equally binding, in other words they carry out the rights and obligations contained in a contract. Sanctions given to both parties in this case PT. Arteri Cipta Rencana Jo PT. Raissa Gemilang and the Implementing Contractor due to not implementing the Agreement stated that the sanctions provided were in the form of written warning, so that PT. Arteri Cipta Rencana Jo PT. Raissa Gemilang can be wise in supervising the implementing contractor, while sanctions for the executing contractor that the disbursement of funds of 5% is held by the Particular Non Vertical Work Unit for Planning and Supervision of the Jambi Provincial National Road, before completing its work properly and correctly and can be accounted for. Keywords: Cooperation Agreement, Road Supervision